Underground radioactivity measurements of meteorites: Development of methods suitable to determine precise terrestrial age of recent falls. (May 2023) - Tymiński, Zbigniew; Hult, Mikael; Krzesińska, Agata M.; Tymińska, Katarzyna; Lutter, Guillaume; Saganowski, Paweł; Marissens, Gerd; Stroh, Heiko; Burakowska, Agnieszka; Ziemek, Tomasz; Stachowicz, Marcin; El-Mallul, Ahmed
Abstract: The L6 chondritic meteorite, HaH-346, fell in Libya. However, neither the exact date of the fall nor the exact size of the original meteoroid or asteroid is known. A specimen of the meteorite, weighing 488 g, was measured using ultra low-background gamma-ray spectrometry in the 225 m deep underground facility HADES. Activation products 22 Na, 26 Al, 60 Co, 57 Co, 54 Mn and 44 Ti were detected. The detection efficiency was determined by 3D scanning the meteorite and introducing this in the computer model of the detector and sample implemented in the MCNP6.2 Monte Carlo code. The activities of 22 Na and 26 Al support the hypothesis that the fall took place on 26 August 2018. Furthermore, the 60 Co and 26 Al activities indicate that the original radius of meteoroid was between 50 and 80 cm, which suggests the mass prior to atmospheric entry was between 2400 and 7300 kg. Highlights: Cosmogonic radionuclides in L6 chondritic meteorite HaH-346 from Libya were studied. The irregularly shaped meteorite was scanned to produce an exact computer model. The computer model was introduced in MCNP6.2 to calculate γ-ray detection efficiencies. The date of fall was determined based on 22 Na, 26 Al and 60 Co massic activities. Based on 26 Al and 60 Co data the size of the original meteoroid was determined.